Chemical Composition and Antibacterial Activities of Eight Plant Essential Oils from Morocco against Escherichia coli Strains Isolated from Different Turkey Organs - Hassna Jaber; Asmaa Oubihi; Imane Ouryemchi; Rachid Boulamtat; Ali Oubayoucef; Brahim Bourkhiss; Mohammed Ouhssine (Biochemistry Research International)
The aim of the present study was to determine the chemical composition of eight plant essential oils and evaluate their antibacterial activity against Escherichia coli strains isolated from different turkey organs. The essential oils were extracted by hydrodistillation and analyzed using gas chromatography-mass spectroscopy. All essential oil yielded high in a range between 2.2 and 3.12%. Gas chromatography-mass spectroscopy (GC-MS) revealed that the major constituents of Thymus vulgaris, Ocimum basilicum, Artemisia herba-alba, and Syzygium aromaticum oils were thymol (41.39%), linalool (37.16%), camphor (63.69%), and eugenol (80.83%), respectively. Results of the E. coli sensitivity evaluated by the standard antimicrobial sensitivity method varied depending on the organ of isolation. Similarly, the essential oils antimicrobial activity determined by the disc diffusion method varied all along within the organs of isolation. T. vulgaris essential oil showed the highest effective antibacterial activity against E. coli isolated from the throat with an inhibition zone diameter value of up to 23.33 mm. However, all the essential oils showed antibacterial activity and the MIC and MBC values were in the range of 1/3000 to 1/100 (v/v) and the ratios MBC/MIC were equal to 1. In conclusion, this study showed that the essential oils could be promising alternatives to overcome E. coli multiresistance in turkey.